Il Museo di Storia Naturale dell'Università degli Studi di Firenze. Le collezioni geologiche e paleontologiche / The Museum of Natural History of the University of Florence.The Geological and Paleontological Collections - Lorenzo Rook; Simonetta Monechi (Firenze University Press, 2021)
The Natural History Museum of the University of Florence, founded in 1775 by Grand Duke Pietro Leopoldo, is one of the oldest scientific museum in the world. With this third volume on the collections of the Geology and Paleontology Section, Firenze University Press continues its series dedicated to the six Sections of the Museum. The first part of the volume shows a detailed and fascinating descriptions of the history of this museum section's collections, the contribution of scholars who from the 17th century endeavoured to expand and study the Florentine geological-paleontological collections, and the importance of the collections to the development of modern geological-paleontological thinking. The second part describes and documents the collections, that are presented in geo-chronological order, divided into the Invertebrate, Vertebrate, Paleobotanical and Geological collections. In the last part are presented the most important activities and research projects, based on this important cultural heritage, carried out by the paleontologists of the University of Florence.